An Application for Royal Men’s Wear Clothing Shop - Bhandare, Prashant; Netaji, Lokhande Shrijeet; Dattatray, Shirke Sarang; Shivshambhu, Naik Yash; Rajesh, Sawale Atharv (International Journal of Computer Sciences and Engineering, 2024)
The research paper titled "An Application for Men’s Wear: An Online Men’s cloth,casual wear Sales and Management System" focuses on developing a digital platform to streamline the sale and management of cloth and fashion products. This project aims to provide an efficient and easy solution for customers to check and buy a variety of cloth items, such as casual wear, fashion wear ,. sunglasses, and more. It incorporates features for managing real-time inventory, processing orders, and facilitating secure payments. The platform caters to both retail and bulk customers, ensuring easy order placement and delivery scheduling. Additionally, the system enhances the overall supply chain management of wearing fashion products, providing a seamless interaction between customers, shop owners, and the admin. This research emphasizes the need for digitization in the garment sector to improve operational efficiency and customer satisfaction.